Performa Itik Albino Jantan dan Betina bedasarkan Pengelompokan Bobot Tetas - Syaifudin, Syaifudin; Rukmiasih, Rukmiasih; Afnan, R. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2015)
Duck’s hatchery industry produces a diverse weight of Day old Duck’s (DOD) because the hatched eggs have diverse weight. The diverse of DOD weight indicates to cause affect to the performance of ducks. Research was conducted to measure the influenceof hatching weight to performance of Alabio duck’s age 0 to 8 weeks. This research used 47 males and 96 females Alabio duck. Alabio’s DODs were separated based on hatching weight, that is small grade (34.39 ± 1.70), medium grade(38.57 ± 0.91), and large grade(43.12 ± 1.98). All ducks had same treatment and maintenance system. This research used randomized completely design with 2x3 factorials of sex and hatching weight. The observed variables were consumption, average daily gain, weight cuts at 8 weeks, feed conversion, and mortality. From this research, hatching weights didn’t influenced to all performances, however sex can influence to daily gain, body weight at 8th  weeks, and feed conversion. Male ducks have daily gain and body weight at  weeks bigger than female ducks. Male ducks have lower feed conversion than female ducks.